2023
DOI: 10.1101/2023.04.12.536550
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of differentially recognized T cell epitopes in the spectrum ofMtbinfection

Abstract: Tuberculosis caused by Mycobacterium tuberculosis is one of the leading causes of death from a single infectious agent. Identifying dominant epitopes and comparing their reactivity in different tuberculosis (TB) infection states can help design diagnostics and vaccines. We performed a proteome-wide screen of 20,610 Mtb derived peptides in 21 Active TB (ATB) patients 3-4 months post-diagnosis of pulmonary TB (mid-treatment) using an IFNgamma and IL-17 Fluorospot assay. Responses were mediated exclusively by IFN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Lindestam Arlehamn et al (5) identified ∼400 CD4 T-cell epitopes in IGRA + individuals, with vast heterogeneity of epitope-specific responses to Mtb. Recently, Panda et al (6) provided evidence for differences in T-cell reactivity against Mtb antigens between TB active and IGRA + individuals. Using longitudinal cohorts and sequential sampling, future investigations should determine when T-cells begin to respond to these differentially recognized peptide antigens and potentially identify signatures of progression and correlates of protection.…”
Section: Antigens Displayed By the Infected Cellmentioning
confidence: 99%
“…Lindestam Arlehamn et al (5) identified ∼400 CD4 T-cell epitopes in IGRA + individuals, with vast heterogeneity of epitope-specific responses to Mtb. Recently, Panda et al (6) provided evidence for differences in T-cell reactivity against Mtb antigens between TB active and IGRA + individuals. Using longitudinal cohorts and sequential sampling, future investigations should determine when T-cells begin to respond to these differentially recognized peptide antigens and potentially identify signatures of progression and correlates of protection.…”
Section: Antigens Displayed By the Infected Cellmentioning
confidence: 99%